A study on the loss of phenol in relation to the shelf life of smoke clam (anodonta grandis). - Martinez, Linda P. (University of the Philippines System, 1978)
Anodonta grandis (freshwater clam) was utilized in this study, smoked and tested for quantity of phenol. The control was processed in the same manners the processing of the smoked sample. Analysis of the samples such as the examination of faecal coliforms (MPN technique), determination of phenol and organoleptic evaluation for changes in general acceptability and texture was carried out. Loss of phenol was determined for storage stability of the samples at chilling temperature (32-35 degree F). With regards to the organoleptic evaluation of the samples, the smoked clam was rated good for its general acceptability on the 4th day f chilled storage up to the 10th day of storage. On the other hand, the unsmoked sample was also rated good but only up to the 8th day of chilled storage. The samples with the highest amount of phenol was kept edible and acceptable up to the 16th day of storage, although the samples soon deteriorated on the 25th day of storage. While the unsmoked samples did not last that long because it deteriorated as early as the 16th day of storage.